2019
DOI: 10.25009/eb.v10i25.2568
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using kefir grains and mesenchymal stem cells in LPS-induced Alzheimer’s disease neuroinflammatory model

Abstract: La enfermedad de Alzheimer (EA) se caracteriza por una acumulación severa de placas amiloides y ovillos neurofibrilares acompañados de disfunciones cognitivas severas que conducen a cambios importantes que afectan la calidad del patrón de vida diaria del paciente. El objetivo del presente estudio es investigar los efectos de la administración de células madre mesenquimales (MSC) y/o granos de kéfir de leche en el modelo de tipo neuroinflamatorio de EA inducida por LPS de manera alternativa. Se observó que una … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
1
8
0
1
Order By: Relevance
“…Our previous results indicated the efficiency of exogenous hydrogen sulphide donor and MSCs (whether systemic or localized administration) in hindering AD progression and even may act as a successful prophylactic protocol due to their anti-inflammatory, antioxidant, immunomodulating response, and Aβ engulfing actions due to the activation of Microglia M2 anti-inflammatory type over M1 microglia proinflammatory type (Anwar et al 2018(Anwar et al , 2019b(Anwar et al , 2021bAnwar 2019). Our results revealed that the administration of NaHS as an exogenous hydrogen sulphide donor and MSCs alleviated neuroinflammatory AD damageable drawbacks on the liver and heart by decreasing Aβ, cholesterol, triglycerides, and, inflammatory cytokines in serum levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results indicated the efficiency of exogenous hydrogen sulphide donor and MSCs (whether systemic or localized administration) in hindering AD progression and even may act as a successful prophylactic protocol due to their anti-inflammatory, antioxidant, immunomodulating response, and Aβ engulfing actions due to the activation of Microglia M2 anti-inflammatory type over M1 microglia proinflammatory type (Anwar et al 2018(Anwar et al , 2019b(Anwar et al , 2021bAnwar 2019). Our results revealed that the administration of NaHS as an exogenous hydrogen sulphide donor and MSCs alleviated neuroinflammatory AD damageable drawbacks on the liver and heart by decreasing Aβ, cholesterol, triglycerides, and, inflammatory cytokines in serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a type of novel gaseous endogenous signaling molecule mainly synthesized from L-cysteine by the action of both cystathionine γ-lyase (CSE) and cystathionine β-synthase (CBS) mammalian enzymes tissue types (Yilmaz et al 2019 ; Jeddi et al 2020 ; Anwar et al 2019a , b ). H 2 S was found to exert potent effects on different types of cells and organs such as smooth muscle cells, endothelial cells, inflammatory cells, brain, heart, liver, and kidney.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV‐1 infection whether reached the CNS directly or indirectly was found to affect different brain regions resulting in severe neuroinflammation and leading eventually to progressive AD pathology. Once reaching the CNS, the virus directly begins to replicate along with the release of pathogen‐associated molecular patterns (PAMPs) and damage‐associated molecular patterns (DAMPs) leading to lipopolysaccharides (LPS) like effects 35–40 . Consequently, this results in the activation and release of pro‐inflammatory cytokines, chemokines, and reactive oxygen species (ROS) associated with TNF‐α and NF‐kB.…”
Section: Herpes Simplex Virus Type 1 (Hsv‐1) and Alzheimer's Diseasementioning
confidence: 99%
“…Menurut Tandalilin (2017) investasi merupakan suatu dana yang ditanamkan pada masa sekarang yang bertujuan memperoleh keuntungan di masa depan. Sedangkan menurut Anwar (2019)…”
Section: Tinjauan Literaturunclassified